ETHICAL ORGANIZATIONAL: IS IT JUST A DISPLAY? - Febriyanti Amol; Forman Halawa; Dedy Iswanto; Baiq Reinelda Tri Yunarni (Journal of Management Small and Medium Enterprises (SMEs), 2023)
The purpose of this research is to find out what are the antecedents and consequences of organizational ethics in the era of Society 5.0 so that they can assist practitioners in making decisions and academics in conducting research related to organizational ethics. This study used a systematic literature review method of 6 articles from the Scopus database relevant to the research problem's formulation. The results show that two factors can influence ethical organizational existence in the era of Society 5.0 i.e. transformational leadership and servant leadership. Meanwhile, the impact of ethical organizational in the organizational system includes moral agency, promotion focus, authentic leadership, work-related stress, employee well-being, creating an ethical organizational, unethical behavior, and job satisfaction. However, this research is still limited to one database and many other things are important to research. So the researcher suggests further research. Keywords: Organizational Ethics; Organizational Behavior; Era of Society 5.0